FRI0470 Cigarette smoking has a dose-dependent relationship with disease activity and correlates with more functional limitation and worse health assessment in the patients with ankylosing spondylitis. (15th June 2017) - Jiang, Y; Liao, Z; Lin, Z; Yang, M; Zhang, Y; Li, Q; Gu, J
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease that mainly affects the axial skeleton by causing inflammatory and osteoproliferative changes in the sacroiliac joints and spinal structures [1]. Cigarette smoking is associated with poor outcome in patients with established and early AS [2]. Objectives: Our study was to investigate the relationship between cigarette smoking and pain, disease activity, functional limitation, and health assessment in Chinese patients with AS. Methods: Patients with AS (n=683) from China took part in a cross-sectional survey. Smoking status was obtained by a standardized questionnaire, involving smoking status (non-smokers, exsmokers, current smokers), the age when starting smoking, cigarette numbers a day and smoking status of family numbers. The Bath AS Disease Activity Index (BASDAI), the Bath AS Functional Index (BASFI), visual Analogue scale of pain, Health Assessment Questionnaire for Spondyloarthropathy (HAQ-S) were analyzed in terms of smoking status and relationship with pack-year history. Results: Of all the 683 patients, 168 are current smokers, while 108 were ex-smokers and 407 patients never smoked. Mean scores of degree and duration of morning stiffness, overall pain, nocturnal back pain, overall back pain, CRP, BASDAI and BASFI score were all higher in the current smoker group compared to those who had never smoked ( P <0.05). In Spearman correlation analysis, pack years of smoking in current smokers were significantly associated with disease duration, morning stiffness (VAS) and duration, nocturnal back pain, overall back pain, CRP, and BASDAI ( P <0.01), and overall pain, BASFI and HAQ-S ( P <0.05). Conclusions: Cigarette smoking has a dose-dependent relationship with disease activity and correlates with more functional limitation and worse health assessment in patients with AS. References: Braun, J. and J. Sieper, Ankylosing spondylitis. Target treatment criteria. Z Rheumatol, 2009. 68(1): p. 30–6. Ward, M.M., et al., Risk factors for functional limitations in patients with long-standing ankylosing spondylitis. Arthritis Rheum, 2005. 53(5): p. 710–7. Acknowledgements: None. Disclosure of Interest: None declared